Goal instability, self-esteem, and vocational identity of high school Portuguese students - Santos, Paulo Jorge (2012)
According to the self-psychology of Heinz Kohut, development of a healthy narcissism that is reflected in a secure sense of self, permits individuals to set and pursue meaningful life goals and maintain a sense ofwell-being, particularly in periods of transition and change. Based on this perspective, the primary purpose of this study was to assess the contribution of goal instability and self-esteem to the vocational identity of Portuguese high school students using a sample of 375 individuals. Additionally, the effect of gender and age on vocational identity was assessed. A regression equation accounted for 32% of the variance of the dependent variable with goal instability emerging as the strongest predictor. Implications for career theory and counseling are discussed.